Conference on serial publications [soundrecording] - Shaffer, Norman J.; American Library Association. Conference (92nd). (Los Angeles, Calif. CREDR Corp., 1974)
Discusses serials department organization and management, general acquisitions problems, bibliographic control of serials, serial services to users, and new techniques such as automation.
Tape 1 (50 min.). General overview / William Huff -- Microforms in serials acquisition and management / Norman J. Shaffer -- Tape 2 (45 min.). National Serials Data Program / Paul Vassallo -- International Standard Bibliographic Description / Serials / Lawrence Livingston.
American Library Association, 92nd annual conference. Audio cassette library for professional librarians.
Keywords: Serials publications -- Congresses; International Standard Bibliographic Description for Serials -- Congresses; Periodicals in microform -- Congresses; Serials control systems -- Automation -- Congresses; Printing; Library science